2010
DOI: 10.1029/2010gl044086
|View full text |Cite
|
Sign up to set email alerts
|

Gravity wave flux retrievals using meteor radars

Abstract: The ability of all‐sky interferometric meteor radars to measure mean wind and high‐frequency gravity wave wind perturbations from meteor radial velocities is assessed. A Monte‐Carlo technique that models line‐of‐sight meteor wind measurements with realistic errors in angle‐of‐arrival and range is used to investigate uncertainties in mean wind and gravity wave wind parameters as a function of meteor echo rate. It is shown that mean horizontal wind speeds are recovered with reasonable accuracy at meteor rates as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 14 publications
(18 reference statements)
2
56
0
Order By: Relevance
“…In this section, we extend the simulations to include a realistic wave field, mainly to investigate the effects of realistic horizontal variations in the perturbed radial velocity fields, similar to the approach taken by others (e.g., Fritts et al, 2010Fritts et al, , 2012Vincent et al, 2010). We simulate a case which is similar to Case 1 of Fritts et al (2010) and Fritts et al (2012), in which we have fixed mean, diurnal tide and semidiurnal tidal amplitudes for the background winds in addition to imposed gravity wave variations.…”
Section: Simulation 2: Realistic Wave Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we extend the simulations to include a realistic wave field, mainly to investigate the effects of realistic horizontal variations in the perturbed radial velocity fields, similar to the approach taken by others (e.g., Fritts et al, 2010Fritts et al, , 2012Vincent et al, 2010). We simulate a case which is similar to Case 1 of Fritts et al (2010) and Fritts et al (2012), in which we have fixed mean, diurnal tide and semidiurnal tidal amplitudes for the background winds in addition to imposed gravity wave variations.…”
Section: Simulation 2: Realistic Wave Fieldmentioning
confidence: 99%
“…Kudeki and Franke, 1998;Thorsen et al, 2000;Vincent et al, 2010). For the case of this simulation, we have assumed that N 3 = 60 statistically independent points exist with which to compute the line-of-sight variances and corresponding wind variances and co-variances.…”
Section: Simulation 1: Statistical Properties Of Momentum Flux Extracmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not originally designed to measure momentum fluxes, standard Skiymet systems nevertheless have a proven ability to do so (e.g. Hocking, 2005;Fritts et al, 2010Fritts et al, , 2012Vincent et al, 2010;Andrioli et al, 2013;de Wit et al, 2014;Placke et al, 2015), albeit with a lower resolution than advanced systems specifically designed for this task (Fritts et al, 2012). The ability to estimate gravity-wave momentum fluxes ultimately relies on being able to separate the contributions to the radial velocity of each individual meteor made by gravity waves from the contributions made by background winds, tides and planetary waves.…”
Section: Data and Data Analysismentioning
confidence: 99%
“…These include Antonita et al (2008) for Trivandrum in the tropics, Clemesha et al (2009) at three low-latitude locations in Brazil, Fritts et al (2010) for Tierra del Fuego at middle latitude, Placke et al (2011b) for Collm at middle latitude, and Placke et al (2011a) at three locations in Europe. While the main aim of Hocking's analysis is the study of GW momentum fluxes, Vincent et al (2010) showed that it is necessary to average for more than one month to get useful results for traditional meteor radars, basically because determination of the momentum fluxes requires the measurement of small vertical velocities. In this paper we present an improvement in the analysis of the traditional meteor radar data that allow us to infer at least a monthly mean of GW momentum fluxes using Hocking's analysis.…”
Section: Introductionmentioning
confidence: 99%